The antidiabetic and antioxidant properties of Athrixia phylicoides aqueous extract : an in vitro and ex vivo assessment - Chellan, Nireshni (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScMedSc)--University of Stellenbosch, 2011.